Demodex spp. Prevalence among University Students - Kaplan, Mustafa; Kelestemur, Neslihan; Baspinar, Serpil (Kafkas Univ, Veteriner Fakultesi Dergisi, 2012)
Demodex spp. was investigated in the 258 university students that participated in the study aimed to investigate Demodex spp. prevalence among university students in Elazig with the methods of cellophane band and standard superficial skin biopsy (SSSB). Of the students, 26 (10.07%) were established as Demodex spp. positive. Demodex spp. prevalence was observed as high among advanced age groups; and Demodex spp. prevalence was also established to decrease with the frequency of taking a shower and antibiotics use in the last 6 months.
Üniversite öğrencilerinde demodex spp. Görülme sıklığı
Keywords: Demodex spp.; University students; Standard superficial skin biopsy